In Silico Analysis of Mechanisms of Maribavir-Induced Inhibition and Drug Resistance Mutations in pUL97 Kinase Structural Prediction with AlphaFold2 - Jocelyne Piret; Guy Boivin (Viruses)
Infections with cytomegalovirus (CMV) can result in increased morbidity and mortality in immunocompromised patients. The pUL97 kinase is a critical enzyme in the regulation of CMV replication. Although it does not phosphorylate deoxynucleosides, this enzyme is involved in the first phosphorylation step of ganciclovir (GCV), a viral DNA polymerase inhibitor. In contrast, maribavir (MBV) is a specific inhibitor of pUL97 kinase activity. In this paper, we analyzed the already-reported amino acid changes, conferring resistance to MBV and cross-resistance to GCV, in the pUL97 protein structure, predicted with AlphaFold2. Docking experiments suggest that MBV is a dual-site inhibitor, targeting ATP binding and substrate phosphorylation. Substitutions that confer resistance to MBV only may directly or indirectly alter the shape of the cavity in the vicinity of the invariant K355 in the putative ATP binding site, without affecting the viral growth. The most frequently encountered T409M substitution may correspond to a gatekeeper mutation. Substitutions that induce cross-resistance to MBV and GCV may directly or indirectly affect the environment of D456 and N461 residues in the catalytic loop, with reduced viral replicative capacity. These results have implications for the clinical use of MBV as well as for the design of novel pUL97 kinase inhibitors.